On some noteworthy alpine or subalpine Hyaloscyphaceae (Leotiales) found in the Pyrenees - Galán Márquez, Ricardo; Raitviir, Ain; Vila i Garcia, Jordi (Revista Catalana de Micologia, 2007)
Four alpine and subalpine species of the Hyaloscyphaceae (Leotiales, Ascomycotina)are described, illustrated and discussed. They wete collected in Catalonia and Andorra, and theyare never been previously reported from the Iberian Peninsula. These are: Lachnum latebricola (Rehm) R. Galán et Raitv., Hyalopeziza nectrioidea (Rehm) Raschle, Incrupila dennisii (Müller)Müller and Lachnellula fuscosanguinea (Rehm) Dennis.